iPad Application for Pain Assessment in Youths with Developmental Disabilities and Complex Communication Needs - (:unkn) unknown (My University, 2016)
Aims: Development of a new pain assessment for youths with communication challenges. The Guard-Putzer Pain Assessment Domains (gPAD) for the iPad was designed and tested as a more universally accessible way for youths, ages 7-to-12 years, with a developmental disability (DD) to express their private pain experiences through self-report. Methods: A two-phase process developed the design for an app, created an interactive prototype, and tested its face validity and user interface. This work included a review of current assessments and pain apps as well as completed a survey to obtain descriptive data on clinical practicality of the gPAD. Fifteen occupational therapists reviewed the gPAD assessment design and reported their experience. Results: Thirteen respondents agreed to the statement that they would use the gPAD for this populatio. School-based practitioners seemed to identify the most significant need for such a new app. Conclusions: Advancement of this app could mainstream the assessment of pain in youths with DD.
Keywords: Developmental Disabilites; Nonverbal; Pain Assessment; Technology